CONSTRAINTS OF TOTAL MASS AND MASS HIERARCHY OF NEUTRINOS FROM COSMOLOGICAL OBSERVATIONS - PUTU AUDITA PLACIDA EMAS - Nim: 20317001, NI
Neutrinos are fermions that come in three spesies (ﬂavors) and are massless in the standard model. However, solar neutrino problem that was solved by neutrino oscillation requires non-zero neutrino mass. Solar and atmospheric neutrino experiments give us the squared mass diﬀerences between mass eigenstates, while from kinematic experiments we get upper limits of individual mass of neutrinos. Oscillation experiments give rise to a further problem regarding the order of neutrino mass known as neutrino mass hierarchy problem, i.e. whether it is normal or inverted hierarchy. Massive neutrinos in cosmology aﬀect Cosmic Microwave Background (CMB) and Large Scale Structure (LSS) formation, besides Big Bang Nucleosynthesis (BBN) that will not be further discussed in the thesis. The impact of neutrino mass appears in the power spectrum of CMB, and in the LSS matter power spectrum as well. Since neutrinos aﬀect events in the universe, we can constrain neutrino properties based on cosmological observations. This thesis is aiming at constraining neutrino total mass from cosmological observations in two hierarchy scenarios, i.e. normal and inverted hierarchies, and also determining neutrino mass hierarchy. To constrain neutrino total mass CosmoMC was employed to perform Bayesian analysis with MCMC algorithm, while neutrino mass hierarchy was determined based on Bayes factor, in which likelihoods of the two hierarchy scenarios were compared. Besides, neutrino individual mass was estimated following Xu and Huang (2018) but in reverse order. Depending on the data set used, diﬀerent total mass constraints were obtained, the tightest constraint comes from combination of CMB + LSS +BAO +Supernova data, i.e. Σmν < 0,183 eV (normal hierarchy) and Σmν < 0,188 eV (inverted hierarchy) with 95% C.L. The Bayes factor analysis prefers nor mal hierarchy, although with weak evidence. A global analysis (incorporating data from oscillation and kinematic experiments) is therefore suggested for a more reliable hierarchy selection. For the selected normal hierarchy, individual mass of neutrinos was determined by incorporating neutrino oscillation data derived from Nu-ﬁt global analysis.